Diagnosis of Human Leptospirosis in a Clinical Setting: Real-Time PCR High Resolution Melting Analysis for Detection of Leptospira at the Onset of Disease: - Esteves, Lisa M. (2018)
Currently, direct detection of Leptospira can be done in clinical laboratories by conventional and by real-time PCR (qRT-PCR). We tested a biobank of paired samples of serum and urine from the same patient (202 patients) presenting at the hospital in an area endemic for leptospirosis using qRT-PCR followed by high resolution melting (HRM) analysis. The results were compared with those obtained by conventional nested PCR and with the serologic gold standard microscopic agglutination test (MAT). Differences were resolved by sequencing. qRT-PCR-HRM was positive for 46 of the 202 patients (22.7%, accuracy 100%) which is consistent with known prevalence of leptospirosis in the Azores. MAT results were positive for 3 of the 46 patients (6.5%). Analysis of paired samples allowed us to identify the illness point at which patients presented at the hospital: onset, dissemination or excretion. The melting curve analysis of Leptospira species revealed that 60.9% (28/46) of patients were infected with L. interrogans and 39.1% (18/46) were infected with L. borgpetersenii, both endemic to the Azores. We validated the use of qRT-PCR-HRM for diagnosis of leptospirosis and for identification of the Leptospira species at the earliest onset of infection in a clinical setting, in less than 2 hours.